2002
DOI: 10.1002/jrs.821
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of molecular crystals at high pressures: VII—Boron Triiodide

Abstract: Raman spectra of solid boron triiodide, BI 3 , at ambient temperature and at pressures up to 5 GPa are reported. Because of drastic but reversible colour changes to the samples and subsequent absorption, measurements at higher pressures were not possible. Four fundamental peaks, assigned as translational, librational, bending and stretching modes, were tracked as a function of pressure. The spectra evolve smoothly and there is no evidence of any structural phase transitions or major molecular distortions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The two peaks observed in the intramolecular region correspond to 1 , the symmetric stretch, and 4 , the degenerate in-plane bend. As for boron triiodide, 1 2 is Raman inactive and 3 , although nominally active, is known to have very low Raman intensity. The small isotopic splittings, which have been observed for 1 in samples at low temperatures, 7,10 cannot be resolved in these experiments at ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two peaks observed in the intramolecular region correspond to 1 , the symmetric stretch, and 4 , the degenerate in-plane bend. As for boron triiodide, 1 2 is Raman inactive and 3 , although nominally active, is known to have very low Raman intensity. The small isotopic splittings, which have been observed for 1 in samples at low temperatures, 7,10 cannot be resolved in these experiments at ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the initially soft crystal stiffens appreciably under external pressure, as was also found for boron triiodide. 1 A comparison of the Raman spectra of these two crystals at high pressures is slightly complicated by the fact that, for BI 3 , measurements were limited to below 5 GPa because of colour changes and resultant absorption effects. 1 As a result, the quadratic dependence of wavenumbers on pressure observed for BBr 3 , with values appearing to approach asymptotic limits, was not found for BI 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous Raman spectra of BI 3 under high pressure reported that there was no evidence of any structural phase transition or notable molecular distortion up to 5 GPa. 5) Our recent results by X-ray diffraction study up to 19 GPa revealed a structural phase transition at 6.9 GPa to a new phase, in which the molecule seemed to dissociate. 6) By applying pressure, the transparent BI 3 crystal gradually became into opaque.…”
Section: Introductionmentioning
confidence: 87%